Маргинальные женщины и насилие: преступницы или жертвы в советском обществе? По материалам Даугавпилсской городской прессы (1953–1964) - Krylova, Iveta (Acta humanitarica academiae Saulensis, 2019)
Women marginalism as a social phenomenon in the Latvian SSR and Daugavpils city, during the period of the “Khrushchev thaw” (1953–1954), had its own characteristic spectrum, also neglect and abuse. In the Soviet period, in 1953–1964 years (time of government of N. Khrushchev in USSR), on the territory of Latvia, in case of the existing social and economic problems – low compensation, shortage of housing, deficit of essential goods and quality manufactured goods, difficult work with little reward and poverty, etc. men’s functions in the family, work and society, understanding of gender roles within the Soviet system and female emancipation, everyday traditions and spread of alcohol consumption among women in Latvian population, became pronounced. That was the foundation for the collapse of traditional patriarchal family and in women’s life occurred such problems as women crime and amoral lifestyle, psychical stress, aggression, neglect and abuse in family in soviet Latvian society. Women marginalism with neglect and abuse as a social phenomenon in the Latvian SSR and Daugavpils city during the period of the “Khrushchev thaw” had a variety of external and internal indicators.Marginal women – criminals or victims in Soviet society? Why were women as perpetrators or as victims of soviet life? How and why could it happen? This problem was vividly expressed in the materials of Daugavpils city press. The article aimed to analyse 23 articles of the Daugavpils press. In the example of women in Daugavpils, the analysis of Daugavpils city press materials, such as “Padomju Daugava” and “Krasnoje Znamja”, includes the history of women’s crimes (1953–1964) within the Soviet system, they are a sources to explore and construct the social reality in the past, formed a basis for reconstruction of crimes and of a social portrait of marginal women, give the chance to establish correlation between age, origin, education level, employment, marital status, the social status, a criminal record and commited neglect and abuse acts. The analysis revealed the influence of the social environment on decline of moral standards and motives, which in interaction with personal and psychological characteristics of women promoted the growth of crime among women.
Keywords: город Даугавпилс; женщина; пресса; советский период; насилие; преступницы; жертвы; советское общество